Effects Of CFD Modelling Configuration On Centrifugal Slurry Pump Casing Wear Prediction - R. Kosmicki (The Southern African Institute of Mining and Metallurgy, 2007)
Wet end components of centrifugal slurry pumps used in the hydraulic transport of solids are subject to substantial erosive wear. Accurate prediction of the casing wear rate and location for a particular duty is beneficial for correct pump selection and design, maintenance planning, and elimination of emergency shutdowns. CFD multiphase simulation using the Eulerian-Eulerian approach is being applied successfully to determine the velocity fields and solids concentration in the centrifugal pump, allowing for accurate predictions of casing wear patterns resulting from sliding abrasive wear. Simulation results for various single domain and multi-domain (multistage) multiphase simulations are discussed. Emphasis is placed on results from a 3-dimensional, multi-stage transient, multiphase simulation and comparison to field data.